Spiritual care: the nurses’ experiences in the pediatric intensive care unit - Nascimento, Lucila C. (2016)
Physical aspects of disease management are often more evident than those related to spirituality or spiritual care. Spirituality may appear more crucial in pediatric intensive care units (PICUs) when patients are experiencing serious illness or end-of-life situations. This paper describes the meaning of spirituality according to nurses who had worked in PICUs and how they provide spiritual care to children and their families. It is an exploratory research using a qualitative approach, including interviews with eleven PICU nurses. Data were analyzed using thematic analysis; two themes were identified: meanings of spirituality and religiosity according to nurses, and the provision of spiritual care to children in the PICU and their families. The interviewed nurses recognized the importance and value of spiritual care and are aware that spiritual needs are considered to be of significantly less importance than physical treatments. Spiritual care was mainly focused on the children’s families; the nurses justified the absence of spiritual care to children, based on lack of time and children’s age and level of consciousness. These results highlight a deficiency in spiritual care in PICUs and demonstrate the need for improved knowledge and demonstrate the need to not only raise awareness of the spiritual dimension of children, adolescents, and their families, but also to enhance discussion and improve general knowledge on the importance of spirituality in the treatment regimen to provide effective holistic care.